Architecture in the Age of Spatial Dissolution - Douglas Darden (Oz, 1987)
Jean Baudrillard has observed that our countryside appears to be an "immense deserted body whose expanse and dimensions seem arbitrary" : both time and space collapse under the "ecstasy of communication."